Estudo sobre a relação entre o crescimento econômico e a desigualdade social. - SANTOS, Ana Clara Almeida; MAGALHÃES, Ashey da Silva; SANTOS, Geovana Almeida dos Santos; FRANÇA, Marcus Vinicius de Medeiros; RODRIGUES, Vinicius Vilarino (128, 2025)
O trabalho analisa a relação entre crescimento econômico e desigualdade, com foco em Mauá (SP), abordando como o desenvolvimento pode aumentar diferenças. Cita Adam Smith, a curva de Kuznets e Thomas Piketty para discutir os impactos sociais dessa dinâmica. O objetivo geral discute como o crescimentoeconômicopode provocar desigualdade, tema cada vez mais debatido na economia atual. Os objetivos específicos do estudo são: investigar a relação entre crescimento e desigualdade, analisar seus impactos, propor políticas inclusivas e avaliar ações que melhorem o bem-estar social. O texto discute a importância de debater a relação entre crescimento econômico e desigualdade social, destacando que o crescimento nem sempre beneficia a todos igualmente.Combase em autores como Piketty e Marshall, defende-seque altos níveis de desigualdade limitam o acesso a serviços e oportunidades, prejudicando o desenvolvimento social. O estudo propõe que políticas públicas, como educação de qualidade e redistribuição de renda, podem tornar o crescimento mais justo e sustentável. O trabalho utilizou pesquisa bibliográfica, documental e descritiva, com abordagem mista, para analisar a relação entre desigualdade e desenvolvimento econômico emMauá (ABC Paulista), com base em fontes acadêmicas e dados locais. O trabalho analisou a relação entre crescimento econômico e desigualdade no Brasil, com foco em Mauá, e concluiu que o crescimento atual não reduz as desigualdades, devido a fatores estruturais e políticas públicas insuficientes. Destacou -se a necessidade de reformas e políticas inclusivas para alcançar um desenvolvimento sustentável e mais justo.

This study examines the relationship between economic growth and inequality, focusing on how these two variables interact and influence each other, with a case study centered on the city of Mauá, São Paulo. The research aims to understand how economic development can impact social and economic disparities and identify thekey factors driving thisdynamic. Drawing from classical and contemporary thinkers such as Adam Smith and Thomas Piketty, the work explores fundamental concepts like the Kuznets Curve and debates surrounding income concentration and wealth distribution. The study highlights that while economic growth is often seen as a sign of progress, it does not necessarily guarantee equitable access to opportunities and resources. High levels of inequality can restrict access to essential services such as education and healthcare, limiting social mobility and reducing overall productivity. Different economic theories offer contrasting views: some suggest that inequality can drive investment and innovation, while others argue it undermines social stability and aggregate demand. This research seeks to contribute to the ongoing debate by analyzing empirical evidence and proposing effective public policies aimed at inclusive growth. Suggested measures include progressive taxation, investment in education, and income redistribution programs. The ultimate goal is to foster sustainable development that not only boosts the economy but also reduces inequality and improves the quality of life for the entire population. The study analyzes the relationship between economic growth and inequality, focusing on Mauá (SP), and explores how development can increase disparities. It references Adam Smith, the Kuznets curve, and Thomas Piketty to discuss the social impacts of this dynamic. The general objective is to examine how economic growth can generate inequality, a topic increasingly debated in today’s economy. The study's specific objectives are to investigate the relationship between growth and inequality, analyze their impacts, propose inclusive policies, and evaluate actions that improve social well-being. The text highlights the importance of discussing the connection between economic growth and social inequality, emphasizing that growth does not always benefit everyone equally. Based on authors such as Piketty and Marshall, it argues that high levels of inequality limit access to services and opportunities, hindering social development. The study suggests that public policies, such as quality education and income redistribution,can make growth fairer andmore sustainable.The research used bibliographic, documentary, and descriptive methods, with a mixed approach, to analyze the relationship between inequality and economic development in Mauá (ABC Paulista),based on academic sources and local data. The work examined the link between economic growth and inequality in Brazil, focusing on Mauá, and concluded that current growth does not reduce inequality due to structural factors and insufficient public policies. The study emphasizes the need for reforms and inclusive policies to achieve more sustainable and equitable development.
Study on the relationship between economic growth and social inequality.
Keywords: Desigualdades sociais; Economia; Gestão e Negócios